IDENTIFIKASI FAKTOR-FAKTOR PENYEBAB KERUSAKAN KOLEKSI DI PERPUSTAKAAN DAN STRATEGI PENCEGAHANNYA - Pratiwi, Ni Putu Mira Adi; Suhartika, I Putu; Ginting, Richard Togaranta (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2022)
Library collections are important things that must be properly maintained because they are vulnerable to damage. If the library collection is damaged it will decrease the quality of the collection so that it cannot be used optimally. Librarians really need to know the factors that affect the damage to library collections. The factors that cause damage are caused by internal factors and external factors. If you already know the factors that affect the damage, it will be easy to take early prevention to maintain and maintain library collections properly.